Research Progress on Small Molecule Adsorbents for Direct Air Capture of Carbon Dioxide (CO₂) - Marru, Marcus; Abeysinghe, Marlon (Journal of Functional Materials and Applied Engineering, 2022)
Carbon capture and storage represents a pivotal strategy for mitigating atmospheric CO₂ accumulation and stabilizing global surface temperatures. Given the low volumetric concentration of CO₂ in ambient air ( 0.415‰) and the high energy penalty associated with conventional adsorption processes ( 21 kJ/mol), developing adsorbents with high CO₂ selectivity, robust structural stability, and low cost is of critical urgency. Small molecule adsorbents have emerged as promising candidates for CO₂ capture owing to their rapid adsorption kinetics, low desorption temperatures (<120 °C), and affordable synthetic costs. This review first outlines the major categories of direct air capture (DAC) adsorbents—including alkali/alkaline earth-based, framework, and amine-based sorbents—and comparatively evaluates their key performance metrics. It then focuses on recent advances in small molecule adsorbents for DAC, with particular emphasis on the design principles and application scenarios of supramolecular host architectures with diverse topologies (linear, multi-arm, cyclic, and cage-shaped). These adsorbents typically incorporate hydrogen-bond donor motifs (e.g., amino, ureido, thiourea, and guanidino groups) that immobilize CO₂ via non-covalent interactions with HCO₃⁻/CO₂ species. The practical deployment of small molecule DAC adsorbents in industrial settings is further summarized. Finally, existing technical bottlenecks are identified, and future research directions for next-generation adsorbent design are proposed.